Context-led capacity building in time of crisis: fostering non-communicable diseases (NCD) research skills in the Mediterranean Middle East and North Africa. Issue 1 (1st January 2019) - Phillimore, Peter; Sibai, Abla M.; Rizk, Anthony; Maziak, Wasim; Unal, Belgin; Abu Rmeileh, Niveen; Ben Romdhane, Habiba; Fouad, Fouad M.; Khader, Yousef; Bennett, Kathleen; Zaman, Shahaduz; Mataria, Awad; et al.
ABSTRACT: Background : This paper examines one EC-funded multinational project (RESCAP-MED), with a focus on research capacity building (RCB) concerning non-communicable diseases (NCDs) in the Mediterranean Middle East and North Africa. By the project's end (2015), the entire region was engulfed in crisis. Objective : Designed before this crisis developed in 2011, the primary purpose of RESCAP-MED was to foster methodological skills needed to conduct multi-disciplinary research on NCDs and their social determinants. RESCAP-MED also sought to consolidate regional networks for future collaboration, and to boost existing regional policy engagement in the region on the NCD challenge. This analysis examines the scope and sustainability of RCB conducted in a context of intensifying political turmoil. Methods : RESCAP-MED linked two sets of activities. The first was a framework for training early- and mid-career researchers through discipline-based and writing workshops, plus short fellowships for sustained mentoring. The second integrated public-facing activities designed to raise the profile of the NCD burden in the region, and its implications for policymakers at national level. Key to this were two conferences to showcase regional research on NCDs, and the development of an e-learning resource (NETPH). Results : Seven discipline-based workshops (with 113 participants) and 6 workshops to develop writing skills (84 participants) were held, with 18 fellowship visits. The 2 symposia in Istanbul and Beirut attracted 280 participants. Yet the developing political crisis tagged each activity with a series of logistical challenges, none of which was initially envisaged. The immediacy of the crisis inevitably deflected from policy attention to the challenges of NCDs. Conclusions : This programme to strengthen research capacity for one priority area of global public health took place as a narrow window of political opportunity was closing. The key lessons concern issues of sustainability and the paramount importance of responsively shaping a context-driven RCB.